2009
DOI: 10.1111/j.1750-3841.2009.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Color Formation in Nitrite‐Free Dried Hams as Related to Zn‐Protoporphyrin IX and Zn‐Chelatase Activity

Abstract: The development of red pigment Zn-protoporphyrin IX (ZPP) in nitrite-free Parma hams was investigated in 5 leg muscles at several stages of processing and the activity of muscle Zn-chelatase was concurrently assayed for its potential role in ZPP formation. A steady increase of the pigment was observed throughout the manufacturing stages at mild temperatures while no development was observed during the prior cold resting phase. The enzyme was partly inactivated according to a muscle-dependent pattern, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 21 publications
(37 reference statements)
5
39
1
3
Order By: Relevance
“…In salted products, the pigment responsible for the typical red color is linked to the zinc protoporphyrin IX (ZPP) molecule (Wakamatsu et al, 2004), generated through a process of substitution of the iron of the heme by a zinc atom (of which pork meat contains much). Studies with model systems (Benedini et al, 2008) or on dried hams (Parolari, Benedini, & Toscani, 2009) highlight the important role of salt in the formation of this pigment by promoting the enzymatic activity of a zinc-chelatase that seems to be involved in this reaction, catalyzing iron substitution by zinc (Wakamatsu et al, 2004). The aim of a study in 2007 was to explore the relationship between lipid and pigment oxidation caused by replacing sodium chloride with potassium chloride at low salt levels (Cheng, Wang, & Ockerman, 2007).…”
Section: Effects Of Salt On Sensory Propertiesmentioning
confidence: 99%
“…In salted products, the pigment responsible for the typical red color is linked to the zinc protoporphyrin IX (ZPP) molecule (Wakamatsu et al, 2004), generated through a process of substitution of the iron of the heme by a zinc atom (of which pork meat contains much). Studies with model systems (Benedini et al, 2008) or on dried hams (Parolari, Benedini, & Toscani, 2009) highlight the important role of salt in the formation of this pigment by promoting the enzymatic activity of a zinc-chelatase that seems to be involved in this reaction, catalyzing iron substitution by zinc (Wakamatsu et al, 2004). The aim of a study in 2007 was to explore the relationship between lipid and pigment oxidation caused by replacing sodium chloride with potassium chloride at low salt levels (Cheng, Wang, & Ockerman, 2007).…”
Section: Effects Of Salt On Sensory Propertiesmentioning
confidence: 99%
“…4.99.1.1) is the endogenous enzyme suggested as being responsible for the formation of ZnPP in meat (Benedini et al 2008). This enzyme is active throughout the processing time of dry-cured hams and is considered to some extent, responsible for the gradual formation of ZnPP (Parolari et al 2016;Parolari et al 2009;Adamsen et al 2006b). The residual activity of this enzyme, even in hams with a low water activity and a high salt concentration, would explain why many authors find a higher ZnPP content at the end of the process (Adamsen et al 2006b;Parolari et al 2009;Parolari et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is active throughout the processing time of dry-cured hams and is considered to some extent, responsible for the gradual formation of ZnPP (Parolari et al 2016;Parolari et al 2009;Adamsen et al 2006b). The residual activity of this enzyme, even in hams with a low water activity and a high salt concentration, would explain why many authors find a higher ZnPP content at the end of the process (Adamsen et al 2006b;Parolari et al 2009;Parolari et al 2016). However, in addition to meat endogenous enzymes, various authors have indicated the existence of other alternative and complex mechanisms that could be involved in this pigment formation and occur simultaneously (Becker et al 2012;Grossi et al 2014;Parolari et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the separated soluble fractions were mixed together with insoluble fraction, ZnPP formation was rescued to a level similar to pork homogenate. Because FECH, considered to be involved in the formation of ZnPP (Becker et al., ; Benedini, Raja, & Parolari, ; Parolari, Benedini, & Toscani, ; Wakamatsu et al., ), is the terminal enzyme of the heme‐biosynthetic pathway in mitochondria, it is likely to be present in the insoluble fraction. In addition, some other insoluble components present in mitochondria, such as protoporphyrinogen oxidases, and protoporphyrinogen IX, are components in the heme‐biosynthetic pathway (Koch et al., ; Poulson, ) and might have a role in ZnPP formation.…”
Section: Resultsmentioning
confidence: 99%